2021
DOI: 10.3390/vaccines9121488
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and Natural Killer Cell Interactions in Cancers: Dangerous Liaisons Instructing Immunosuppression and Angiogenesis

Abstract: The tumor immune microenvironment (TIME) has largely been reported to cooperate on tumor onset and progression, as a consequence of the phenotype/functional plasticity and adaptation capabilities of tumor-infiltrating and tumor-associated immune cells. Immune cells within the tumor micro (tissue-local) and macro (peripheral blood) environment closely interact by cell-to-cell contact and/or via soluble factors, also generating a tumor-permissive soil. These dangerous liaisons have been investigated for pillars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
7
0
1
Order By: Relevance
“…The effect of natural killer cells (NK cells) on angiogenic properties of neutrophils has been indicated [173]. By producing IFNγ and GM-CSF, NK cells have been shown to activate neutrophils and induce their surface expression of CD11b, CD62L, and CD64 [173].…”
Section: Mechanisms Regulating Pro-and Anti-angiogenic Activity Of Neutrophils In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of natural killer cells (NK cells) on angiogenic properties of neutrophils has been indicated [173]. By producing IFNγ and GM-CSF, NK cells have been shown to activate neutrophils and induce their surface expression of CD11b, CD62L, and CD64 [173].…”
Section: Mechanisms Regulating Pro-and Anti-angiogenic Activity Of Neutrophils In Cancermentioning
confidence: 99%
“…After the activation by NK-derived factors, such neutrophils supported tumor angiogenesis by releasing VEGF and MMP-9. Moreover, they upregulated ARG1 expression, resulting in tumor growth [173], possibly by suppressing anti-tumoral T cell functions. On the other hand, Ogura et al demonstrated that NK-derived IFNγ is able to inhibit VEGF expression of neutrophil [174], once again showing the complexity of the cell-cell interactions in tumor angiogenesis.…”
Section: Mechanisms Regulating Pro-and Anti-angiogenic Activity Of Neutrophils In Cancermentioning
confidence: 99%
“…Neutrophils, which are important innate cells involved in the clearance of acute bacterial and viral infections, may help activate APCs, NK cells, and T cells [32] , [33] . To evaluate whether neutrophil activation is increased or decreased by C—S/M treatment, we next assessed neutrophil activation in CTX-injected mice following pre-treatment with C—S/M.…”
Section: Resultsmentioning
confidence: 99%
“…FcγRIIIb/CD16b is mainly expressed by neutrophils and also negatively regulates neutrophil activities in the TIME [ 39 , 41 ]. Even though the interaction between neutrophils and NK cells in TIME is unclear, neutrophils can enhance NK-derived interferon (IFN)γ to suppress tumor progression and angiogenesis [ 42 , 43 , 44 ]. In addition, this study found that the FCGR3B expression level accurately predicts the TB status (AUC = 81.7%) and patient survival (high expression causes poor prognosis in OS, p = 0.0016).…”
Section: Discussionmentioning
confidence: 99%